2020
DOI: 10.1136/archdischild-2020-319837
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infection in neonates: a systematic review

Abstract: ObjectiveTo summarise currently reported neonatal cases of SARS-CoV-2 infection.MethodsA search strategy was designed to retrieve all articles published from 1 December 2019 to 12 May 2020, by combining the terms ‘coronavirus’ OR ‘covid’ OR ‘SARS-CoV-2’) AND (‘neonat*’ OR ‘newborn’) in the following electronic databases: MEDLINE/Pubmed, Scopus, Web of Science, MedRxiv, the Cochrane Database of Systematic Review and the WHO COVID-19 database, with no language restrictions. Quality of studies was evaluated by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0
10

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 36 publications
(9 reference statements)
10
84
0
10
Order By: Relevance
“…Transmission was reported for term and preterm infants and for vaginal and c-section modes of delivery. These data were supported by other reviews which concluded that neonatal COVID-19 infection is uncommon, almost never symptomatic, and that the rate of infection is no greater when the baby is born vaginally, breastfed, or allowed contact with the mother (16,17).…”
Section: Vertical Transmissionsupporting
confidence: 67%
See 1 more Smart Citation
“…Transmission was reported for term and preterm infants and for vaginal and c-section modes of delivery. These data were supported by other reviews which concluded that neonatal COVID-19 infection is uncommon, almost never symptomatic, and that the rate of infection is no greater when the baby is born vaginally, breastfed, or allowed contact with the mother (16,17).…”
Section: Vertical Transmissionsupporting
confidence: 67%
“…Indeed, the main concern in this instance is the mother's ability to follow the strict contact precautions to avoid spreading the virus via the recognized horizontal routes. Therefore, it is important that mothers be counseled on suitable protocols for breastfeeding and breast pump usage (12,17,26,32).…”
Section: Discussionmentioning
confidence: 99%
“…Other findings may include mild thrombocytopenia, normal or mildly raised inflammatory markers (C-reactive proteins, procalcitonin), as well as elevated liver enzymes, creatine kinase, alkaline phosphatase, and lactate dehydrogenase. 9,13,15,16 There were no specific radiologic features although it appeared milder compared to adults, with unilateral or bilateral infiltrates. The ground-glass opacities, multiple bilateral lobular and segmental consolidations in the peripheral lung particularly are shown more clearly by chest computer tomography than the chest x-ray.…”
Section: Diagnosismentioning
confidence: 96%
“…Predominant observed symptoms were fever or temperature instability, followed by gastrointestinal symptoms such as diarrhea and vomiting, abdominal distention, and poor feeding. 15,16 The majority of neonates that were experiencing respiratory symptoms did not require intubation and mechanical ventilation. 16 A study from Italy stated that only 1 out of 10 neonates with respiratory symptoms needed mechanical ventilation, but concomitant condition (prematurity) may have contributed to the clinical status, thus, cannot be excluded.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation